Kekuatan Mengikat UDHR 1948 terhadap Negara Anggota PBB, Khususnya Indonesia - Rukmana Amanwinata (Jurnal Hukum IUS QUIA IUSTUM, 2000)
Although, the Constitution of Human Rights 1948 accepted by General Assembly of the United Nations on December 10 1948 does not have a tightening power yurisdically, it has a more tightening power in the form of moral bound. This is due to an assumptionissued by civilized nations of the United Nation members that the contain of the Article of Human Rights constitutes a minimum standard for human rights. Indonesia, which was admitted as a member of the United Nations after the Article of Human Rights 1948 issued, has morally responsible for this point. Therefore, this issue was also stated in the Temporary Constitution of the Republic of lndonesia 1950, and has been reflected on the 1945 Constitution following other regulations.